Light of truth and fire of love : a theology of the Holy Spirit - Badcock, Gary D. (Grand Rapids, MI William B Eerdmans Publishing Company, 1997)
"The Doctrine of the Holy Spirit has often been a neglected theme in Christian thought. In Light of Truth and Fire of Love Gary D. Badcock attempts to redress this theological imbalance and to reassert the centrality of the doctrine of the Spirit in Christian theology." "Badcock begins by surveying what both the Old and New Testaments have to say about the Spirit. Next he traces the history of the theology of the Spirit, examining a number of crucial episodes and questions in the field of pneumatology in the history of Christian thought, and then proceeds to develop a contemporary theology of the Spirit. Badcock goes on to relate this theology of the Spirit to the theological enterprise initiated by Karl Barth earlier in this century - a return to the doctrine of the Trinity as the framework for Christian reflection. Setting forth the positive and negative results of much of contemporary trinitarian theology, Badcock ultimately makes a case for a balanced doctrine of the Word and the Spirit in which neither is subordinated to the other."--BOOK JACKET.
Introduction: The Holy Spirit in Christian Theology -- Spirit in Biblical Perspective. The Old Testament ; Paul and Luke-Acts ; John -- The Patristic Consensus. The Shape of Patristic Pneumatology ; The Deity of the Holy Spirit -- The Filioque Controversy. The Western Pneumatological Tradition ; A Theological Asssessment of the Filioque Doctrine ; The Eastern Position -- The Reformation Tradition. The Word and the Spirit ; Justification and the Spirit
Includes bibliographical references (pages 274-296) and indexes.
Keywords: Holy Spirit; Holy Spirit -- History of doctrines; Word of God (Christian theology); Word of God (Christian theology) -- History of doctrines